The Economic Consequences of Heightened Materiality Uncertainty: An Auditing Perspective - Huang, Ying; Li, Ningzhong; Zhang, Jieying; Zhou, Xiaolu (The Accounting Review, 2024)
ABSTRACT Using a Supreme Court ruling that rejected the use of “bright-line” rules previously relied upon in evaluating materiality claims, this study examines how heightened materiality uncertainty impacts audit pricing. We expect the heightened uncertainty to make it more difficult for auditors and clients to assess materiality and to reach a consensus on materiality assessment, which increases audit effort and engagement risk, leading to higher audit fees. Consistent with this prediction, we find that after the ruling, audit fees increase significantly for treatment firms in the circuits using bright-line rules in the pre-ruling period, relative to control firms not affected by the ruling. This effect is stronger when auditors have lower quality or lower industry expertise, and when investors have more diverse opinions. We also find that for firms audited by low-expertise auditors, auditor turnover due to auditor-client disagreement on materiality-related issues increases significantly for treatment firms relative to control firms. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: K2; M41; M42.